Exploring challenges and opportunities encountered by private health facilities in Lusaka urban, Zambia: A case study of selected private health facilities in Lusaka Urban, Zambia. - Khondowe et al. (Rwanda Medical Journal)
INTRODUCTION: The role of healthcare provision has been shouldered by governments globally, primarily through public sector institutions. In Africa, health systems in both private and public health institutions encounter significant challenges and opportunities. Zambia, in its pursuit of universal healthcare, is incorporating private facilities to increase access to quality healthcare. However, there's inadequate research on the challenges and opportunities encountered by these facilities. This study aimed to explore the challenges, solutions, and opportunities encountered by private health facilities in Lusaka, Zambia, with the goal of providing information for policy, decision-making, and future research.